2020
DOI: 10.1038/s41467-019-14025-0
|View full text |Cite
|
Sign up to set email alerts
|

Rad50 zinc hook functions as a constitutive dimerization module interchangeable with SMC hinge

Abstract: The human Mre11/Rad50 complex is one of the key factors in genome maintenance pathways. Previous nanoscale imaging by atomic force microscopy (AFM) showed that the ringlike structure of the human Mre11/Rad50 complex transiently opens at the zinc hook of Rad50. However, imaging of the human Mre11/Rad50 complex by high-speed AFM shows that the Rad50 coiled-coil arms are consistently bridged by the dimerized hooks while the Mre11/Rad50 ring opens by disconnecting the head domains; resembling other SMC proteins su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…The coiled-coil structure, which is conserved across the SMC proteins and all known Rad50 orthologs ( de Jager et al., 2004 ; Paull, 2018 ; Stracker and Petrini, 2011 ; Syed and Tainer, 2018 ), comprises a heptad repeat pattern wherein the first and the fourth residues are hydrophobic to allow the association of antiparallel helices via their hydrophobic faces ( de Jager et al., 2001 ; Truebestein and Leonard, 2016 ; van Noort et al., 2003 ). The apex of the RAD50 coiled coil consists of a zinc (Zn)-hook domain by which two MRE11-RAD50 complexes can dimerize to form intra- and intermolecular complexes that have been proposed to bridge DNA ends ( Hohl et al., 2015 ; Hopfner, 2014 ; Park et al., 2017 ; Paull, 2018 ; Stracker and Petrini, 2011 ; Syed and Tainer, 2018 ; Tatebe et al., 2020 ). It has also been recently suggested that MRE11-RAD50 complexes could promote DNA tethering of sister chromatids at stalled forks by facilitating Cohesin loading ( Delamarre et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The coiled-coil structure, which is conserved across the SMC proteins and all known Rad50 orthologs ( de Jager et al., 2004 ; Paull, 2018 ; Stracker and Petrini, 2011 ; Syed and Tainer, 2018 ), comprises a heptad repeat pattern wherein the first and the fourth residues are hydrophobic to allow the association of antiparallel helices via their hydrophobic faces ( de Jager et al., 2001 ; Truebestein and Leonard, 2016 ; van Noort et al., 2003 ). The apex of the RAD50 coiled coil consists of a zinc (Zn)-hook domain by which two MRE11-RAD50 complexes can dimerize to form intra- and intermolecular complexes that have been proposed to bridge DNA ends ( Hohl et al., 2015 ; Hopfner, 2014 ; Park et al., 2017 ; Paull, 2018 ; Stracker and Petrini, 2011 ; Syed and Tainer, 2018 ; Tatebe et al., 2020 ). It has also been recently suggested that MRE11-RAD50 complexes could promote DNA tethering of sister chromatids at stalled forks by facilitating Cohesin loading ( Delamarre et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although the flexibility of the RAD50 coiled-coil domain has prevented determination of its whole structure at atomic resolution ( Käshammer et al., 2019 ; Park et al., 2017 ), several studies suggested that this domain participates in the regulation of MRN functions by propagating information from the Zn-hook domain to the globular domain ( Hohl et al., 2011 , 2015 ; Park et al., 2017 ). Analyses using crystallographic microscopy, cryo-electron microscopy (cryo-EM), and high-throughput single-molecule microscopy suggested that dimers of the ATP-bound MRE11-RAD50 intracomplex (M 2 R 2 ) mostly adopt a ring conformation that can interact and scan the DNA homoduplex to recognize the DNA end and trigger ATM/Tel1-dependent DDR ( Deshpande et al., 2014 ; Hopfner, 2014 ; Käshammer et al., 2019 ; Myler et al., 2017 ; Tatebe et al., 2020 ). A model suggested that upon ATP and DNA binding, the MRE11-RAD50 intracomplex undergoes a conformational switch, leading to the interaction of intermolecular coiled-coil domains and resulting in a rod-shaped structure.…”
Section: Introductionmentioning
confidence: 99%
“…The position in the middle of the protein where the two coiled-coil domains fold on themselves is characterized by a zinc hook domain. This zinc hook domain also facilitates dimerization of the RAD50 protein [ 29 , 78 , 79 ]. Our analysis of COSMIC mutations revealed a hotspot frameshift mutation within the Zn finger domain (K722Rfs*14) [ 75 , 80 , 81 , 82 ] ( Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
“… 186 High-speed AFM was used to determine the global architecture of these human, yeast, and bacterial complexes including the impact of the Nbs1 subunit on the human MRN complex. 187 Tatebe and colleagues 187 showed that the ring structure of Mre11/Rad50 repeats an open-close action at the head, but the hook between the Rad50 dimer remains closed. They demonstrated that the global architecture and conformational features of the Mre11/Rad50 complex were conserved.…”
Section: Afm Studies Of Dna–protein Interactionsmentioning
confidence: 99%